Legal Regulation of Parallel Import in the States of the Eurasian Region - V. P. Kirilenko; D. M. Guseinova (Евразийская интеграция: экономика, право, политика, 2024)
The article is devoted to the problem of regulating parallel imports in the countries of the Eurasian region, which is significant in the conditions of the modern world economy. The relevance of this issue is related to the economic sanctions applied to such states of the Eurasian region as the Russian Federation and the Republic of Belarus. The legal regulation of issues of protection of intellectual property rights in Russia, Belarus, Kazakhstan, China, and Azerbaijan is analyzed. Special attention is paid to the consideration of the practice of the Constitutional Court of the Russian Federation, as well as legal acts regulating the rights of both copyright holders and importers and consumers, who are subject to the consequences of certain decisions of copyright holders who do not consent to the import of goods into different states.Aim. Research of the legal regulation of the institution of parallel imports in the states of the Eurasian region in the context of economic sanctions.Tasks. Analysis of regulations governing the protection of intellectual property rights in the states of the Eurasian region, research of the main directions of parallel imports in the states of the Eurasian region, as well as identification of the main legal problems associated with the legalization of parallel imports in the region.Methods. Comparative legal and cross-temporal analysis of international and national regulations in the field of antitrust, copyright and customs law, as well as the study and analysis of general scientific literature and the formation of one’s own conclusions during the research.Results. As a rule, the states of the Eurasian region have established the national principle of exhaustion of rights to a trademark, and the international principle is used as an exception for certain groups of goods. The legalization of parallel imports raises several formal questions about the compliance of permission to import without the consent of the copyright holder with the international obligations of various states.Conclusions. In connection with the introduction of economic sanctions against some states of the Eurasian region, parallel imports are an effective mechanism for protecting the domestic market from abuses by copyright holders who unreasonably deny importers the right to distribute goods. Also, one of the methods to neutralize the consequences of sanctions regulation is to use the markets of other countries in the Eurasian region, which do not directly prohibit parallel imports.